Effective ways South African brands can market on instagram to influence purchase intentions: a user's perspective - Rambarun, Simone Nicolette (My University, 2018)
Background - Although Instagram is one of the fastest growing social network sites, research dedicated to this platform has been limited. Purpose – The purpose of this research is to investigate how South African brands could optimally utilise Instagram as a marketing channel that positively influences consumer buying behaviour. Research Methodology/Approach – A quantitative approach was used for this study. Research data was collected using an online survey, with a total of two hundred and seventeen South African Instagram users who made up the final sample. Findings – The outcomes confirmed that all hypothesised statements were significant and thus, accepted. The main findings further revealed that user perspectives played a valuable role in the co-creation process and reiterated that types of content (on Instagram) positively affected the study’s constructs; customer engagement, brand awareness and electronic-word-of-mouth. In addition, these constructs proved to positively impact consumer purchase intentions. Research limitations – The present study focuses on a niche sample which consists of South African Instagram users only. It is recommended that future researchers incorporate a global user perspective from Instagram users across the world, to determine other key factors that might positively impact consumer purchasing behaviour. Managerial implications – Marketing practitioners spend a significant amount of time in determining the driving forces that boost sales. The verified relationships between types of content, brand awareness, customer engagement and electronic-word-of-mouth reiterates the need for all stakeholders to incorporate Instagram as a powerful channel of marketing in their social media strategies.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Strategic Marketing 22 June 2018
Keywords: Instagram (Firm); Online social networks; Internet marketing; Social media